2020
DOI: 10.3389/fmicb.2020.01975
|View full text |Cite
|
Sign up to set email alerts
|

Constant Light Exposure Alters Gut Microbiota and Promotes the Progression of Steatohepatitis in High Fat Diet Rats

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) poses a significant health concern worldwide. With the progression of urbanization, light pollution may be a previously unrecognized risk factor for NAFLD/NASH development. However, the role of light pollution on NAFLD is insufficiently understood, and the underlying mechanism remains unclear. Interestingly, recent studies indicate the gut microbiota affects NAFLD/NASH development. Therefore, the present study explored effects of constant light exposure on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
3
27
0
1
Order By: Relevance
“…LPS, as the most important component of the Gram-negative bacteria membrane, binds to Toll-like receptor 4 (TLR4) and activates innate immune response. In our study, elevated level of this receptor expression was observed in the HFD group ( Figure 5A ; Wei et al, 2020 ). LPS transfer to the TLR4 is catalyzed by local and systemically LPS binding protein.…”
Section: Discussionsupporting
confidence: 62%
“…LPS, as the most important component of the Gram-negative bacteria membrane, binds to Toll-like receptor 4 (TLR4) and activates innate immune response. In our study, elevated level of this receptor expression was observed in the HFD group ( Figure 5A ; Wei et al, 2020 ). LPS transfer to the TLR4 is catalyzed by local and systemically LPS binding protein.…”
Section: Discussionsupporting
confidence: 62%
“…Studies have shown that the protein expressions of ZO-1 and occludin are reduced in adenocarcinoma of the digestive tract and that the intestinal barrier is impaired, followed by increased intestinal permeability ( Han X. et al, 2019 ). Simultaneously, butyrate in colon contents could decrease expressions of occludin-1 and ZO-1 in colon tissue ( Wei et al, 2020 ). In the present study, intestinal barrier was injured after colon cancer modelling, accompanied with infiltration of lymphocytes, monocytes in the intestinal mucosal layer, and a decreasing in intestinal tight junction proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Constant light exposure with HFD induces glucose abnormalities, insulin resistance, inflammation, and liver steatohepatitis in mice, which is associated with less abundance of Butyricicoccus , Clostridium , and Turicibacter , also known as butyrate producers. These changes correlate with decreased butyrate levels in colon contests, decreased colon expressions of occludin-1 and ZO-1, and increased serum LPS and mRNA expression of liver LPS-binding protein [ 139 ]. As described earlier, A. muciniphila exhibits protective effects on intestinal permeability.…”
Section: Hfd and Bile Acidsmentioning
confidence: 99%